Transposition of Directive 2014/95/EU – Do macroeconomic determinants affect non-financial reporting harmonisation?. Issue 5 (5th July 2021) - Stefanescu, Cristina Alexandrina
Abstract : Purpose: The purpose of this study is to explore the underlying assumption that macroeconomic factors (legal, cultural, social, financial and/or economic) might support or constrain countries' decisions to timely and fully transpose the Directive 2014/95/EU (EUD) on non-financial information disclosure. Design/methodology/approach: The research design relies mainly on exploratory factors analysis, regression techniques (linear, logistic and multinomial) and additional robustness and sensitivity tests, all performed to ensure the reliability and trustworthiness of the results. Findings: The results reveal that the directive's transposition process is driven more by regulatory and social legitimisation forces than by economic and financial pressures. Stronger governance and weaker interests' protection ensure appropriate compliance with new regulations, while highly educated countries express openness towards developing accounting systems that enhance information transparency. Practical implications: The results are useful for practitioners currently engaged in the directive's implementation process, academics interested in challenging debates concerning this topic and regulatory bodies to better support its full enactment. Originality/value: This paper approaches the newsworthy topic of non-financial information disclosure settled by the EUD and marks an essential step towards harmonising non-financial reporting across Europe. It enriches the scientific literature through the first empirical analysis that sheds light on its explanatory drivers.